QUALITY OF HUMAN RESOURCES ON GOJEK CONSUMER SATISFACTION IN TANGERANG WITH SERVICE QUALITY AS A MEDIATING VARIABLE - Peter Rajagukguk; Woro Dwi Hartanty; Bambang Haryono; Isroni Isroni (Jurnal Scientia, 2023)
The development of communication technology encourages changes in all aspects of life, both social, cultural, economic and various other aspects, including transportation. People are experiencing a transformation in their daily activities, shopping online, interacting with social media, and even traveling using online applications. This research aims to determine human resource and service quality's influence on consumer satisfaction of Gojek online motorcycle taxis in Tangerang. This descriptive quantitative statistical research type uses SmartPls 4, outer model and inner model measurements. Data collection methods were questionnaires and interviews, with a sample size of 100 people. Non-probability sampling technique with quota sampling. The research results show t statistic > t table and sig value. > P value. So, the quality of human resources has a positive and significant effect on consumer satisfaction. Service quality has a positive and significant effect on consumer satisfaction. HR quality has a positive and significant effect on service quality. The quality of human resources has a significant effect on consumer satisfaction through service quality. The simultaneous R square test of 0.666 means that the quality of human resources and service quality influence consumer satisfaction by 66.6%, including the moderate influence category.